Reflective Analysis of the Transition of a Face-to-Face Principal Preparation Program into an Online Format - Robert Moody; Regi Weiland (The Advocate, 2011)
This paper addresses the redesign of a face-to-face principal preparation program into an online program. An action research project began in 2004, gathering data to guide the transition. A key element was the commitment of program faculty to reflect throughout the process by considering their personal technological strengths, weaknesses, and needs, altering as needed. Data collection included investigating competing programs, feedback from principal interviews, focus groups, instructor evaluations, enrollment and retention data, and current curriculum. The results of the study, including growth in student enrollment, data from program exit exams, and student perceptions of the program are provided.